Diversitas Gulma pada Budidaya Padi dan Jagung di Lahan Pasang Surut Desa Banyu Urip Kecamatan Tanjung Lago - Karlin Agustina; Yursida Yursida (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2015)
The experiment about Diversity of weeds on rice and maize cultivation in the tidal-land Banyu Urip village subdistrict Tanjung Lago was conducted from November 2013 until Desember 2013. The purpose of the experiment is determinate the dominant weed species in cultivation of rice and maize in the tidal-land, to evaluate the results of weed control, and can be a basic weed control recommendations. The method used is squared method. The results showed that the dominant weeds in rice crops with highests sum dominance ratio (SDR) is: Ludwigia octovalvis, Fymbristilis littoralis, Alternanthera philoxeroides and Cyperus kylingia. Dominant species in maize planting is: Alternanthera phyloxeroides, Paspalum conjugatum, Borreria alata, and Euphorbia hirta. The use of a single active ingredient â€œisopropylamine â€“ glifosatâ€ in weed control in the tidal-land have not been able to effectively control weeds both broadleaf weeds, puzzles or grass. Mechanical methods of weed control on weeds with stoloniferous will increasingly dominant weed.